The role of π?π stacking and hydrogen-bonding interactions in the assembly of a series of isostructural group iib coordination compounds - Senge, Mathias (My University, 2019)
The supramolecular chemistry of coordination compounds has become an important research domain of modern inorganic chemistry. Herein, six isostructural group IIB coordination compounds containing a 2-{[(2-methoxyphenyl)imino]methyl}phenol ligand, namely dichloridobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)zinc(II), [ZnCl2(C28H26N2O4)], 1, diiodidobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)zinc(II), [ZnI2(C28H26N2O4)], 2, dibromidobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)cadmium(II), [CdBr2(C28H26N2O4)], 3, diiodidobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)cadmium(II), [CdI2(C28H26N2O4)], 4, dichloridobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)mercury(II), [HgCl2(C28H26N2O4)], 5, and diiodidobis(2-{(E)-[(2-methoxyphenyl)azaniumylidene]methyl}phenolato-κO)mercury(II), [HgI2(C28H26N2O4)], 6, were synthesized and characterized by X-ray crystallography and spectroscopic techniques. All six compounds exhibit an infinite one-dimensional ladder in the solid state governed by the formation of hydrogen-bonding and π–π stacking interactions. The crystal structures of these compounds were studied using geometrical and Hirshfeld surface analyses. They have also been studied using M06-2X/def2-TZVP calculations and Bader's theory of `atoms in molecules'. The energies associated with the interactions, including the contribution of the different forces, have been evaluated. In general, the π–π stacking interactions are stronger than those reported for conventional π–π complexes, which is attributed to the influence of the metal coordination, which is stronger for Zn than either Cd or Hg. The results reported herein might be useful for understanding the solid-state architecture of metal-containing materials that contain MIIX2 subunits and aromatic organic ligands.
PUBLISHED
cited By 1
Keywords: π-stacking; Hydrogen bonding; Noncolvalent interactions; Metallosupramolecular assembly; Crystal structure; Coordination compound; Group IIB